Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

6x−3y=−6 solve for y

Sagot :

Answer:

y = 2 (x + 1) or y = 2 + 2x

Explanation:

Move all terms that don't contain y to the right side and solve.

Answer:

 y=2x+2

Step-by-step explanation:

  6x−3y=−6

6x−3y+6=−6+3y

    6x+6  =3y

           y=2x+2

Hope you got it

If you have anything just ask me

If you think this is the best answer please mark me as brainliest